Mad men. Season three [videorecording (DVD)] - Hamm, Jon, 1971-; Moss, Elisabeth, 1982-; Kartheiser, Vincent, 1979-; Hendricks, Christina, 1975-; Jones, January, 1978-; Weiner, Matthew (Lionsgate, 2010)
At the office, the firings continue; Don is brought in to save the day on a PR campaign only to have the rug pulled out from under him; Peggy and Paul get stoned while working on an ad campaign; Sally steals money from her grandfather; Don had reservations about a misguided potential client; Betty has hallucinations of her dead father as she delivers her baby; Don and Betty renew their love affair while on a business trip.